CHANGE OF THE PLAY IN THREE GENERATIONS - Gökhan GÜNEŞ (Fırat University, 2019)
The aim of this research is to examine the changes of play in time. The study was carried out with 30 grandmothers and 20 grandfathers of teacher candidates who study at Hacettepe University. It is tried to understand the play and change of play in time according to grandparents. For this purpose, it was used an interview form prepared by taken expert opinion. Four main chapters constitute of interview form, these are; demographic information, point of view about play, play process and change of play in time. It was evaluated data according to content analyses method. Pearson Correlation analyses used for determining the relationship between changes of play in time according to the generations. According to the analysis; it was seen that when participants describe play, they focus on the role of fun rather than the educational value of it. Moreover, it was determined that there are many changes in the way children play between different generations. Especially; there is a quite change in play choices in new generation compare to the first two generations. Physical activities, outdoor games and playing with friends are not preferred by new generation. It was seen that new generation prefer to play with technological toys, to play in indoor environments and to play alone. Due to the fast and uncontrolled development in play industry which affects to differences of play trend in generations, makes children get lonely in social regard and in